Impact of reproductive factors on breast cancer subtypes in postmenopausal women: a retrospective single-center study - Au, Alexandra von; Klotzbücher, Mona; Uhlmann, Lorenz; Boudewijns, Mark; Michel, Laura L.; Wallwiener, Markus; Heil, Jörg; Golatta, Michael; Rom, Joachim; Sohn, Christof; Schneeweiss, Andreas; Schütz, Florian; et al. (Archives of gynecology and obstetrics, 2017)
PurposeSome reproductive factors are well-known general risk factors for breast cancer (BC). On the other hand, BC subtypes also have a high prognostic value. Correlations, however, that link these risk factors to the development of a particular one of the different BC subtypes are still poorly understood. The primary objective of our study was to assess the influence of different reproductive factors (duration of breastfeeding, parity, and age at first childbirth) on pathological BC subtypes. Secondarily, we correlated body mass index (BMI), age at primary diagnosis, and smoking behavior with tumor subclasses.Patients and methodsWe performed a retrospective chart review of 1082 patients with BC who had been treated for postmenopausal BC at the Heidelberg University Hospital during the period 2009-2014. For statistical analysis, different types of correlation analysis as well as a logistic regression model were used.ResultsRelating to the primary objective, we found that patients with luminal-like BC had significantly fewer children than patients with triple-negative or HER2-positive subtype tumors (P = 0.027). Concerning the duration of breastfeeding, patients with a luminal A-like tumor had a significantly lower mean nursing period than patients with other subtypes (P = 0.012). Furthermore, patients who did breastfeed presented with a significantly lower number of hormone receptor-positive tumors (estrogen receptor-positive, P = 0.04; progesterone receptor-positive, P = 0.017) but the highest rate of HER2-overexpressing malignancies (P = 0.011). Moreover, late first childbirth was associated with the occurrence of luminal tumors (OR 0.952; P = 0.041). Regarding our secondary aim, higher BMI (P = 0.031) and higher age at primary diagnosis (P = 0.038) were both found to be significantly associated with luminal-like BC.ConclusionThe results suggest a correlation of the occurrence of luminal-like BC subtypes with low parity and short or no duration of breastfeeding. Prospective investigations are needed for further confirmation and to evaluate the molecular basis of our findings.
Gesehen am 27.07.2018